Extracellular Vesicles and Their Importance in Human Health - Gil De Bona, Ana; Antonio Reales Calderon, Jose (IntechOpen, 2020)
Extracellular vesicle is a wide term that involves many different types of vesicles. Almost all the cell types studied secrete vesicles to the extracellular environment related to cell - cell communication. Extracellular vesicles have been found in different biological fluids, such as blood, milk, saliva, tears, urine, and cerebrospinal fluid. These vesicles transport different molecules, including mRNA, proteins, and lipids, some of them cell type specific that make them ideal biomarkers in both health and disease conditions. However, their contribution to different conditions is not well understood. The aim of this book is to provide an overview of the extracellular vesicles in the human body, how they are internalized, and their participation in several diseases.